[tex]a) 4 \frac{1}{4} +6\frac{1}{2} -8 \frac{1}{3}=\frac{17}{4}+\frac{13}{2} -\frac{25}{3}=\frac{51+78-100}{12}=\frac{29}{12} =2\frac{5}{12}\\b) 2 \frac{1}{5} +3 \frac{1}{2} -\frac{1}{4}=\frac{11}{5}+\frac{7}{2}-\frac{1}{4}=\frac{44+70-5}{20}=\frac{109}{20}=5\frac{9}{20}\\c) 2\frac{5}{6} -(-\frac{1}{5} )+5=\frac{17}{6}+\frac{1}{5}+5=\frac{85+6+150}{30}=\frac{241}{30}=8\frac{1}{30}[/tex]
[tex]e) -3\frac{1}{8} +(-2 \frac{1}{5} +\frac{3}{4} )=-\frac{25}{8}-\frac{11}{5} +\frac{3}{4}=\frac{125-88+30}{40}=\frac{67}{40}=1\frac{27}{40} \\f) \frac{8}{15} -(-1\frac{2}{5} +2\frac{1}{4} )+3 \frac{1}{2} =\frac{8}{15}+\frac{7}{5}-\frac{9}{4}+\frac{7}{2}=\frac{320+840-1350+2100}{600} =\frac{1910}{600}=\\\frac{191}{60}=3\frac{11}{60} \\[/tex]